THE EFFECT OF INFANT EXERCISE ON WEIGHT GAIN BY AGE IN INFANTS AGED 6–12 MONTHS IN TULUNGREJO VILLAGE - Anita Rahmawati; Rosyidah Alfitri (Yayasan Nuraini Ibrahim Mandiri, 2026)
Growth baby is indicator important health and nutritional status , one of which is assessed through improvement appropriate weight​ age . Babies aged 6–12 months ideally experience increase weight of around 340–560 grams per month . One of the intervention non-pharmacological which can support growth is infant exercise, which is thought to capable increase activity physical , quality sleep , and lust Eat baby . Research This aim For analyze the effect of infant exercise on improvement weight according to age in babies 6–12 months of age . Research use quasi-experimental design with non-randomized control group pretest–posttest design approach . Sample A total of 28 babies met criteria inclusion , consisting of over 14 babies in the group treatment and 14 babies in the control group control group​ treatment given infant exercise during four week , while group control get maintenance routine . Body weight is measured before and after intervention . Data analysis using Paired t-test and Independent t-test with level 5 % significance show that group treatment experience improvement overweight​​ tall compared to group control . Paired t-test shows difference meaningful before and after intervention (p = 0.000), while the Independent t-test also showed difference improvement significant weight gain between second group (p = 0.000). Conclusion: Infant exercise is proven to effective increase weight according to age in babies age 6–12 months